The Problematic of Small-Scale Land Acquisition (Less than 5 Hectares) for Public Interest Development - Donna Okhtalia Setiabudhi (Faculty of Law, Hasanuddin University, 2016)
Land acquisition for public interest development is stipulated in Act No. 2 of 2012 concerning Land Acquisition for Development of Public Interest. One arrangement of land acquisition in legal substances that have been formed are small-scale land acquisition (less than 5 hectares), but it is still governed by very vague and thus susceptible to the multi-interpretation and raises doubts in its implementation. This paper discusses the problematic that arise due to unclear regulations concerning small-scale land acquisition and to provide solutions to these problems. Based on the discussion the authors concluded first, the problematic of small-scale land acquisition is the arrangement of land acquisition that is so vague that there is no clarity regarding the procedures for determining of location, the phase of land acquisition, which excludes public consultation, there is no regulation regarding preventive measures against the impact for the community around location of land acquisition. Second, the solution could be found to this problem is a regulation of small-scale land acquisition should ideally be regulated more comprehensively considering that small-scale land acquisition allows the emergence of adverse effects for the community around location of land acquisition so that the stages of planning and preparation that is set for the large-scale land acquisition is similarly applied for small-scale.